A Variance Shift Model for Detection of Outliers in the Linear Measurement Error Model - Babak Babadi; Abdolrahman Rasekh; Ali Akbar Rasekhi; Karim Zare; Mohammad Reza Zadkarami (Abstract and Applied Analysis)
We present a variance shift model for a linear measurement error model using the corrected likelihood of Nakamura (1990). This model assumes that a single outlier arises from an observation with inflated variance. The corrected likelihood ratio and the score test statistics are proposed to determine whether the ith observation has an inflated variance. A parametric bootstrap procedure is used to obtain empirical distributions of the test statistics and a simulation study has been used to show the performance of proposed tests. Finally, a real data example is given for illustration.